Clinical Symptoms of Patient with Heart Failure in Dr. Soetomo General Hospital: A Descriptive Study - Niki Kusuma Bangsa; Rochmad Romdoni; Subagyo Subagyo (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Heart failure (HF) has emerged as a cardiovascular disease with high prevalence in developing countries. The highest number was expected to increase over the next few decades. Moreover, most people with HF do not show specific symptoms earlier, thus death often occurs. This study was undertaken to give an insight into the clinical symptoms and risk factors of HF.Methods: This cross-sectional study utilized medical records from Dr. Soetomo General Hospital between 6 months (July-December 2016). Eligibility criteria included female patients diagnosed with HF at the hospital with a classification of NYHA I-IV. Risk factors data from the participants such as hypertension, diabetes mellitus, dyslipidemia, body mass index (BMI), smoking status, and history of cardiovascular disease were collected. Clinical symptoms were reported descriptively.Results: From 84 patients admitted with HF in the hospital from July until December 2016, 53 were males (63.1%). In all groups, hypertension (35.6%) was the highest prevalence risk factor, followed by diabetes mellitus (25.3%), and a history of cardiovascular disease (17.2%). In this study, the most common symptom was shortness of breathing, contributing to 72.6%, followed by chest pain (10.7%), and body weakness (6%).Conclusion: This study concluded that most of the respondents were male, aged 46-65 years old. The highest risk factor that contribute to an HF was hypertension. The most common symptom in patients with HF in the hospital was shortness of breathing. Studies further emphasize the need for primordial prevention related to symptoms and risk factors of HF.